Word edge tones in Spanish prenuclear accents - Eva Estebas Vilaplana (Estudios de Fonética Experimental)
In this paper we analyse the alignment patterns of H prenuclear accents in Spanish so as to examine whether prenuclear rises in declarative sentences can be interpreted as a sequence of an L* pitch accent and an H word edge tone. A production test was designed consisting of 20 pairs of ambiguous sentences with a different word boundary location (e.g. bebo vinos “I drink wines” vs. ve bovinos “(s)he sees cows”). Sentences were read by four speakers of Peninsular Spanish. The results showed that for all speakers the H is always anchored right after the accented syllable. However, H alignment does seem to be affected by the stress distribution of words, since the F0 peak is more displaced in proparoxytones that in paroxytones and in paroxytones than in oxytones, suggesting the presence of a loosely aligned H word edge tone. Furthermore, two perception tests (a discrimination test and an identification test) were carried out to investigate whether H alignment can be a helpful cue to identify otherwise ambiguous sentences. The results showed that words with a stress on the penultimate or antepenultimate syllable are more easily distinguished than words with a final accent, which indicates that H alignment differences due to word position are an important cue for word-boundary identification.